Correlates of the levels of various immunoreactive hormones and the quality of buffalo (Bubalus bubalis) semen during different seasons - SIDHU, K S; GILL, H K (The Indian Journal of Animal Sciences, 2013)
Immunoreactive progesterone, prolactin and luteinizing hormone (LH) are present in the seminal plasma of buffalo. Variation in the levels of these hormones during different seasons of the year were nonsignificant (p<0.01). Higher levels of prolactin and LH were accompanied by semen of poor quality. The coefficient of multiple linear correlation (R2) between the levels ofimmunoreactive progesterone, prolactin and LH and various semen characteristics revealed that immunoreactive progesterone showed more interaction with prolactin than with LH. Variations up to 35% in the levels of protactin and 23% in the levels of LH could be due to variations in semen characteristics. The biological significance of the presence of immunoreactive progesterone, prolactin and LH is discussed.